MENINGKATKAN AKTIVITAS, KETERAMPILAN BERPIKIR KRITIS, DAN HASIL BELAJAR SISWA MENGGUNAKAN KOMBINASI MODEL PBL, STAD, DAN SNOWBALL THROWING PADA MUATAN IPAS DI SDN PANGERAN 1 BANJARMASIN - Qansha Saputri Hakim; Asrani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The problems in this research is the low level of activity and critical thinking skills which result in low learning outcomes in the content of IPAS. The purpose of this research is to describe teacher activities, analyze the improvement of student activities, critical thinking skills, and learning outcomes. This research used Classroom Action Research which was carried out in 4 meetings. The subject of this research is 24 students in grade III of SDN Pangeran 1 Banjarmasin, in semester II of the 2024/2025 school year. The results of the research showed that the teacher's activities at meeting 4 had been carried out with the criteria of "Very Good". Student activity at meeting 4 increased with the "Very Active" criterion. The critical thinking skills at meeting 4 increased with the criteria of "Highly Skilled". The learning outcomes of students in the cognitive aspect classically at meeting 4 became 92% complete. The learning outcomes of the affective aspect classically at meeting 4 became 96%. The learning outcomes of the psychomotor aspect classically at meeting 4 became 88%.